An adaptive and cooperative MAC protocol in vehicular ad hoc network: design and performance analysis. (17th November 2020) - Dang, Duc Ngoc Minh; Ngo, Quynh T.; Le-Trung, Quan; Le, Long Bao
Vehicular ad hoc network is the key technology to enable the intelligent transportation system. VANET should provide reliable broadcasting to support the safety-related application. It is also required to effectively transmit service-related data. With the rapid development of the internet of vehicles, medium access control (MAC) protocols for VANET are expected to be more adaptive and scalable to the network size; so that the MAC protocol can operate effectively in supporting the massive number of connections. This paper proposes a multi-channel MAC protocol, namely AC-MAC, that enables multi-hop transmission of safety application data leveraging cooperation among vehicles. The proposed MAC protocol ensures the reliability of safety message transmission and the effective utilisation of channel resources. Moreover, the MAC mechanism also has the ability to adapt to different network conditions.